Efficient capacitance sensing for wireless health monitoring system. - Che Mustapha, Nurul Arfah; Alam, A. H. M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (IIUM Journal Publication, 2016)
This paper presents a low power capacitance to voltage converter (CVC) circuit using two differential amplifier circuits, two Schottky rectifier diodes constructed in symmetrical manner and combined with instrumentation amplifier circuits. The differential capacitance to voltage simulation work has been realized with cheap discrete components. Combination energy from solar, vibration and heat is expected to be used to source the capacitance circuit. Constant dc voltage of 3 V has been used to source the CVC circuit in this work. It is found by the simulation, the converter circuit consumes 3.9 mW of total power, operates at 40 kHz using 400 mV excitation signal. The circuit is able to detect changes of capacitance from 4 – 12.5 pF using reference capacitance of 5 pF. Sensitivity of 0.132 mV for 1 fF capacitance change has been observed in the circuit. This circuit is suitable for wireless health monitoring system.